Specific Nature of Spatial Awareness Formation of the Bachelor of Technical Higher Education Institution of Ukraine During the Basic Course - Artemenko, Dmytro; Artmenko, Olga; Martynenko, Serhii; Cherednychenko, Nataliia (Journal of Technical Education and Training, 2020)
A formed spatial awareness is one of the main professionally important quality of a young professional, a graduate of Technical and Vocational Education and Training (TVET) and higher technical education institutions. The carried out analysis of graphical preparation in the process of school studying has allowed to ascertain that enrollees of basic technical specialties are prepared not at sufficient level, the spatial awareness is formed at a low level. The shortlisting of future students on the ground of the availability of elementary spatial awareness is not conducted. The formation of spatial awareness of students during the basic course in higher technical education institutions of Ukraine is rested exclusively on instructors. As a result of the literature sources and normative documentation analysis, we have developed a structural-stage model of the process of spatial awareness formation of a bachelor of higher technical education institutions which includes the initial, basic and professional stages. There were defined problems in the first stage of training at the level of basic knowledge of the spatial awareness, and was suggested to begin studying with consideration and solving of problems on the plane with the subsequent transfer of the solution to the spatial model. The transfer to the inverse process can be accomplished only after full understanding of the interrelation of the carried out geometric actions and learning the techniques and methods of solving metric and positional problems with two and three-dimensional figures. A logframe of classes conduction and measures for its realization have been developed. Carried out experimental investigations in regards to application of the specified approach in the training process have made it possible to increase the level of formation of the basic level of spatial awareness at the beginning of training.